#TITLE_ALTERNATIVE# - AQUARINI (NIM 10104022), NARITA
Bank Asset and Liability Management (ALM) Model is a mathematical model that manage the bank's fund allocation. This Model used by bank to get an optimal profit and ensure the bank liability. In this final project the Bank Asset and Liability Management (ALM) Model is developed by the multiperiod stochastic linier programming. The model has objective function which maximizes the expected profit. The model's constraints have several functions. One of the constraint's functions is to represent the government regulation about banking. Others functions are to keep the bank's liquidity and cash flow. In general this final project explains The ALM model from the basic theory to the applications.